Differential response of bovine T-cell lines to membrane and soluble antigens of Theileria parva schizont-infected cells - Brown, W.C.; Sugimoto, C.; Conrad, P.A.; Grab, D.J. (Wiley, 1989)
Summary T–cell lines generated from Theileria parva–immunc cattle were used to identify antigens associated with schizont–infected lymphoblastoid cells. Homo–genates prepared from T. parua–infected cells were fractionated by differential centrifugation, and antigenically distinct soluble and membrane–bound antigens were detected by the differential stimulation of cell lines derived from two animals. Activity in the soluble fraction was not attributable to either a mitogen or interleukin 2. Activity in the membrane fraction was associated with schizont membranes as indicated by the presence in this fraction of a parasite protein detected by immunoblot analysis using a schizont–specific monoclonal antibody. Elimination of intracellular schizonts over time, using the anti–theilerial drug, parvaquone, resulted in a concomitant loss of antigenicity in infected cells and in subcellular fractions prepared from drug–treated cells, demonstrating that stimulation of Theileria–sptahc helper and cytotoxic T–cell responses is associated with the presence of the parasite.